Spatial heterogeneity of low-birthweight deliveries on the Kenyan coast - Musau, MM; Mwakio, S; Amadi, D; Nyaguara, A; Bejon, P; Berkley, JA; Snow, RW; Kamau, A (BioMed Central, 2023)
Background Understanding spatial variations in health outcomes is a fundamental component in the design of effective, efficient public health strategies. Here we analyse the spatial heterogeneity of low birthweight (LBW) hospital deliveries from a demographic surveillance site on the Kenyan coast.